2019
DOI: 10.1021/acs.jafc.9b03477
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Metabolism in Postharvest Tea (Camellia sinensis L.) Leaves: Variations in Color Values, Chlorophyll Derivatives, and Gene Expression Levels under Different Withering Treatments

Abstract: The freshness and color quality of postharvest tea leaves can be markedly prolonged and retained by proper preservation measures. Here, we investigated the dynamic changes of chlorophyll and its derivatives in postharvest tea leaves under different low-temperature treatments using natural withering as a control. Chlorophyll decomposition was found closely related with chlorophyllide, pheophorbide, and pheophytin. Low-temperature withering could slow chlorophyll degradation in postharvest tea leaves via signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 50 publications
(77 reference statements)
3
37
0
1
Order By: Relevance
“…In addition to the aroma and taste, color is a key trait used for measuring tea quality. The color of the dry tea leaves and the resulting liquid influences consumer preferences and purchasing decisions ( Yu et al, 2019 ). The pigments that contribute to tea colors generally include chlorophyll, carotenoids, and anthocyanins, of which chlorophyll is the most important pigment for determining green tea quality ( Suzuki and Shioi, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aroma and taste, color is a key trait used for measuring tea quality. The color of the dry tea leaves and the resulting liquid influences consumer preferences and purchasing decisions ( Yu et al, 2019 ). The pigments that contribute to tea colors generally include chlorophyll, carotenoids, and anthocyanins, of which chlorophyll is the most important pigment for determining green tea quality ( Suzuki and Shioi, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…For oolong tea, it has been found that the total content of glycosidically bound volatiles (GBVs) gradually increased at the withering step and then remarkably increased after the fixing step at 230 • C [4]. The dehydration stress during withering can promote the special flavors of various teas by inducing significant changes in the gene transcription and amounts of tea flavor compounds [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, glutamate and GABA synthesized from glutamine might cause an increase in the relative content of GABA [30]. Additionally, a decrease in chlorophyll pigment during withering reduces glutamate content [31].…”
Section: Discussionmentioning
confidence: 99%